Analysis of Students Mathematical Concept Understanding at MTs Al-Mahrus in Terms of Learning Style - Nurbaiti Octiviani Pulungan; Cut Latifah Zahari (Riemann: Research of Mathematics and Mathematics Education, 2025)
The The ability to understand concepts is the ability to understand and account for an idea as well as the ability to think logically, critically, creatively and innovatively. The research objective of this study is to look at the profile of the ability to understand concepts through PjBL learning in terms of students' learning styles in understanding mathematical concepts in class VIII-A statistics material at MTs Al-Mahrus Mabar. The method used in the research is descriptive qualitative research. The research location is Jalan RPH LINK.IV Mabar Hilir Medan and the research time was carried out in the 2023/2024 academic year. The research subjects were 6 students from 22 students, where the researcher chose 2 students each with visual, auditory and kinesthetic learning styles based on the student learning style questionnaire that had been given. The researcher's data collection method used four techniques, namely observation, interviews, questionnaires and concept understanding ability tests. Data analysis is carried out by reducing data, presenting it, and drawing conclusions. The research results show that students with kinesthetic learning styles understand mathematical concepts better than students with visual and auditory learning styles. Students with a kinesthetic learning style are able to understand three of the four indicators of conceptual understanding, while students with a visual style, the same as students with an auditory learning style, are only able to understand two of the four indicators of conceptual understanding.